Role of Audit and Governance Committee for internal Shariah audit effectiveness in Islamic banks - Azam Abdelhakeem Khalid (Emerald Publishing Limited, 2020)
The purpose of this study is to explore the role of Audit and Governance Committee (AGC) for internal Shariah auditing's effectiveness in Bahrain's Islamic banks.This paper employed two-stage approach, i.e. collecting and analysis of data. In this paper, the interviews and literature review on AGC and internal Shariah auditor were conducted as these respondents are considered vital to Islamic banks.This paper posited that in building internal Shariah audit effectiveness' conceptual framework, the Islamic worldview theory may be employed as the theoretical foundation. Based on the theory, it was suggested that the Islamic bank's auditors and governance committees may enhance the internal Shariah auditors' effectiveness.In view of the roles of AGC on internal Shariah audit effectiveness, the current exploratory research contribute to enhance the limited knowledge about AGC by describing the practices of Bahraini Islamic banks in terms of composition, roles/duties and responsibilities and operations. This study also adds to the body literature of AGC effectiveness by identifying roles, duties and responsibilities of characterizing more active AGC and suggesting that these AGC could have a positive impact on internal Shariah audit effectiveness in Bahraini Islamic banks. Overall, this paper provides important insights for Board of Director's member can refer to AGC roles, duties and responsibilities to conduct a self-diagnosis of current practice.This paper uniquely seized Islamic world view for Islamic banks' AGC.